Correlation between fear of cancer recurrence and levels of mindfulness in patients with gastric cancer: mediating effects of couple support - LU Li; ZHENG Min; ZHANG Yu; ZHANG Kaili (Yixue xinzhi zazhi)
Objective To explore the mediating effect of marital support between the correlation of fear of cancre recurrence (FCR) and the level of mindfulness in patients with gastric cancer.Methods Gastric cancer patients admitted to the department of gastroenterology in the Second Affiliated Hospital of Xuzhou Medical University from August 2020 to August 2022 were selected, and all patients underwent radical gastrectomy treatment. A general information survey, the Fear of Progression Questionnaire-Short Form (FoP-Q-SF), the Marital Support Questionnaire, and the Mindfulness Attention Awareness Scale (MAAS) were used to investigate the included study subjects. Spearman rank correlation analysis was used to explore the relationship between FCR, mindfulness level, and marital support. The Bootstrap method was used to verify the mediating effect of marital support on the FCR and mindfulness level in gastric cancer patients.Results A total of 120 patients were included. The total FoP-Q-SF score was (27.37±6.03), of which 22 patients had psychological dysfunction due to fear of disease progression. The total score of marital support was (56.81±18.03). The total MAAS score was (54.72±7.75). The results of correlation analysis showed that the FCR and its scores were negatively correlated with the scores of the patients' mindfulness level and total score and scores for each dimension of spousal support (P